COMPARING ILBIL, IBL, AND CONVENTIONAL MODELS: SELF-REGULATED LEARNING IN MATHEMATICS ACHIEVEMENT - Vera Dewi Susanti; Swasti Maharani; Tri Andari; Rika Wulandari (Program Studi PGSD Universitas Flores, 2026)
Teaching models currently play a crucial role in enhancing educational quality and improving student learning outcomes. The purpose of this study was to compare the effectiveness of three learning models—ILBIL (Inquiry Learning Based on Information Literacy), IBL (Inquiry-Based Learning), and conventional learning — on students’ mathematics learning outcomes in the topic of three-dimensional geometry. A quantitative approach was applied using a posttest control group design. The study population consisted of 143 students, and a cluster-random sampling technique was used to select 89 students from three classes. Data were collected through observations, questionnaires, and tests. The data were analyzed using analysis of variance (ANOVA) with a 5% significance level, as performed in SPSS 25.00 for Windows. The results revealed: (1) a significance value of 0.000, which is less than 0.05, indicating that the ILBIL model was more effective than both the IBL and conventional models in terms of students’ learning outcomes; (2) a significance value of 0.196, which is greater than 0.05, suggesting that self-regulated learning did not significantly affect students’ learning outcomes; and (3) a significance value of 0.306, which is greater than 0.05, showing that the interaction between self-regulated learning and the learning model did not significantly influence students’ learning outcomes.